Um predador generalista na fronteira entre ecossistemas: interações tróficas e os processos ecossitêmicos bromelícolas - Piccoli, Gustavo Cauê de Oliveira [UNESP] (2015)
Predation is a kind of ecological interaction that strongly influences the structure and dynamic of not only terrestrial and aquatic ecosystems, but also in a connective way in the ecotones where the borders lines are thin. Tank bromeliads provide a naturally mixed microcosm, composed by both terrestrial and aquatic elements, being suitable for the study of across-ecosystems predation effects, and the consequences in the bromeliad ecosystem effects. In our study we aimed to elucidated behavioral and ecological issues of the terrestrial predator, the spider Corinna demersa (Corinnidae), and its relationship with aquatic organisms and the ecosystem processes present in the tank bromeliads of the Atlantic Rainforest in the southeastern coast of Brazil. In the first chapter we identify the exclusive interaction between this predator and tank bromeliads, being the habitat where the spider spends its whole life, showing particular behaviors adapted to this environment. In the second chapter the direct and indirect effects of this predator in an aquatic and simplified community were identified, being the intensity of the trophic cascade compared when initiated by the terrestrial predator, by the aquatic and both. The main results point out the distinct lethal effects between terrestrial and aquatic predators and their antagonistic interaction, which results in the total survivor of aquatic preys. We documented the influence of the quality of detritus on the intensity of trophic cascades triggered by predators over the fragmentation rate of detritus. A cascade generated by the aquatic predator may be more intense than that generated by the terrestrial predator in a specific type of detritus, although it could be either diminished or enhanced due to the interactive effect of predators over detritivorous. In the last part, we verified the effect of the food availability by the presence of a terrestrial prey, on the interaction between C. demersa ...